PENERAPAN PERMAINAN EDUKATIF PUZZLE UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF ANAK USIA DINI DI TK KRISTEN UWEN PANTAI KELOMPOK B1 KECAMATAN TANIWEL TIMUR - Manakutty, Natalia; Souhaly, Sela; Hasan, Hamsiah; Halamury, Mercy (Institut Agama Kristen Negeri (IAKN) Ambon, 2023)
The purpose of this study was to find out the application of educational puzzle games to improve early childhood cognitive abilities in Uwen Pantai Christian Kindergarten Group B1, East Taniwel District. The method used is Classroom Action Research, through Planning, Observation, Action and Reflection. The subjects in this study were 20 children. The application was carried out up to cycle 3. Based on the results of the actions carried out in cycles I, II, and cycle III, the results in cycle I the ability to remember gets 44% results, the ability to understand gets 46% results, to apply gets 44% results, to analyze gets 44%, to evaluate gets 44% results, to create gets 44 %, and the percentage results are 44% with 20 students. In cycle II the ability to remember gets 55%, the ability to understand gets 66%, the ability to apply 53%, the analyze gets 49% results, the evaluate gets 47% results, the create gets 57% results and 55% percentage. In Cycle III the ability to remember gets 65%, to understand 75%, to apply gets 62%, to analyze gets 65% results, the evaluate gets 61%, the create gets 62%, and the percentage results are 64%. Keywords: Puzzle Games, Improving, Children's Cognitive